The Potency of Alpinia galanga as Natural Antioxidant - Dian Ratih Laksmitawati; Diah Kartika Pratami; Wahyu Widowati; Hanna Sari Widya Kusuma; Cahyaning Riski Wijayanti; Rizal Rizal (Majalah Obat Tradisional, 2022)
An antioxidant is a chemical compound that can bind free radicals in the body. Reactive oxidative species (ROS) is a reaction that involves oxygen. ROS consists of free radicals and non-radical ones. The imbalance between ROS and antioxidants can cause oxidative stress, one of the factors contributing to the development of numerous diseases. This study aims to evaluate the possible antioxidant activity of lengkuas extract (LE), which may be employed as a medicine component to reduce ROS. The method that used in this research were total phenolic content, total flavonoid content, 2,2 diphenyl 1 picrylhydrazyl (DPPH) scavenging, hydrogen peroxide (H2O2), NO scavenging, 2,2′-Azinobis(3-Ethylbenzthiazoline-6-Sulfonate) (ABTS), and ferric reducing antioxidant power (FRAP). The result shows that the TPC of LE was 6.80 ± 0.34 (GAE) µg/mg with gallic acid standard and the TFC was 3.39 ± 0.06 µg/mg by quercetin standard. The IC50 value of LE were 121.20; 87.65; 139.94; 181.09 µg/ml by ABTS, DPPH, NO, and H2O2 assay respectively. The scavenging activity of LE was increased with a higher concentration in every method. In conclusion, Alpinia galanga has the potential as an antioxidant. Thus, it can be widely consumed or used as a mixture in medicine to reduce ROS.